Global 3D Radiation Magnetohydrodynamic Simulations of Accretion onto a Stellar-mass Black Hole at Sub- and Near-critical Accretion Rates - Jiahui Huang; Yan-Fei Jiang; Hua Feng; Shane W. Davis; James M. Stone; Matthew J. Middleton (The Astrophysical Journal, 2023)
We present global 3D radiation magnetohydrodynamic simulations of accretion onto a 6.62 solar-mass black hole, with quasi-steady-state accretion rates reaching 0.016–0.9 times the critical accretion rate, which is defined as the accretion rate for powering the Eddington luminosity, assuming a 10% radiative efficiency, in three different runs. The simulations show no sign of thermal instability over hundreds of thermal timescales at 10 r _g . The energy dissipation occurs close to the mid-plane in the near-critical runs and near the disk surface in the low–accretion rate run. The total radiative luminosity inside ∼20 r _g is about 1%–30% of the Eddington limit, with radiative efficiencies of about 6% and 3%, respectively, in the sub- and near-critical accretion regimes. In both cases, self-consistent turbulence generated by the magnetorotational instability leads to angular momentum transfer, and the disk is supported by magnetic pressure. Outflows from the central low-density funnel, with a terminal velocity of ∼0.1 c , are seen only in the near-critical runs. We conclude that these magnetic pressure–dominated disks are thermally stable and thicker than the α disk, and that the effective temperature profiles are much flatter than those in the α disks. The magnetic pressures of these disks are comparable within an order of magnitude to the previous analytical magnetic pressure–dominated disk model.